2019
DOI: 10.1089/thy.2019.0278
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Variants and Their Risks for Malignancy in Cytologically Indeterminate Thyroid Nodules

Abstract: Background: Gene panels are routinely used to assess predisposition to hereditary cancers by simultaneously testing multiple susceptibility genes and/or variants. More recently, genetic panels have been implemented as part of solid tumor malignancy testing assessing somatic alterations. One example is targeted variant panels for thyroid nodules that are not conclusively malignant or benign upon fine-needle aspiration (FNA). We systematically reviewed published studies from 2009 to 2018 that contained genetic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 90 publications
4
49
0
1
Order By: Relevance
“…For cases with gene fusions, the ROM was 91% (10 of 11 cases) for the THADA/IGF2BP3 fusion, similar to the report by Goldner and colleagues (positive predictive value, 100%) 9 . Although, only 2 of our cases contained the PAX/PPARγ fusion, both were malignant, consistent with ATA classification as a high‐risk mutation (95%) 5 .…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For cases with gene fusions, the ROM was 91% (10 of 11 cases) for the THADA/IGF2BP3 fusion, similar to the report by Goldner and colleagues (positive predictive value, 100%) 9 . Although, only 2 of our cases contained the PAX/PPARγ fusion, both were malignant, consistent with ATA classification as a high‐risk mutation (95%) 5 .…”
Section: Discussionsupporting
confidence: 89%
“…Our study demonstrated a 100% ROM when any of these were present. As reported by previous studies, solo mutations in the PTEN , DICER1 , E1F1AX , TSHR , and TP53 genes were associated with benign pathologic follow‐up 9 …”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…For Afirma XA, PPV is reported either for the specific alteration identified or for alterations of that gene. These values were derived from validation data, 3,15,16 a systematic review of the published literature 17 and its periodic update, or real-world experience among consecutively identified patients with available surgical histopathology. 18 These PPVs are reported to their nearest quartile (eg, PPV 50% or 75%), except for those >95% (BRAFV600E, NTRK fusions, and RET fusions) and >99% (medullary thyroid cancer classifier positive).…”
Section: Positive Predictive Valuementioning
confidence: 99%
“…The prediction of malignancy of thyroid nodules continues to improve. Sonographic features of thyroid nodules alone are not sufficient to predict malignancy risk 3 . Each year, as many as 50,000 patients in the United States undergo unnecessary thyroidectomy because of the difficulty in distinguishing benign thyroid nodules from thyroid cancers preoperatively.…”
Section: Introductionmentioning
confidence: 99%